Innovation and play to enhance learning in academic libraries An interview of Andrew Walsh - Kiuru, Eerika; Asplund, Janika (Signum, 2017)
Andrew Walsh visited Helsinki in March 2017 and organized a workshop “Making educational escape room style activities” for Finnish library professionals together with The Finnish Research Library Association (STKS) and its Information Literacy group. The day was full of fun and expertise.